Kota Layak Anak Berbasis Collaborative Governance - Noverman Duadji; Novita Tresiana (Sawwa: Jurnal Studi Gender, 2018)
This paper describes the development of collaborative governance-based city/district, so it is hoped that children's policies and programs with holistic, integrative and sustainable character will be developed. This paper is the result of research aimed at: 1) mapping the problem and potential of children as central issue that can be developed as development issue; 2) develop an ideal city/district ideal child model. The research method used qualitative descriptive. Research location in Lampung Province. The results of the study describe children problems including child abuse, disability children, children faced with law and abandoned babies due to policies and programs that are not partial to children, policies are partially, segmentatively and sectorally arranged, no cooperation/partners with other institutions. The existence of local policy potential in the form of various policies and local regulations, the number of social institutions of children into social capital is strong physically and socially in building collaborative model/partnership.